Rekonstruksi Kewajiban Nafkah dalam Rumah Tangga: Analisis Yuridis Normatif terhadap Peran Istri sebagai Pencari Nafkah dalam Hukum Islam - Dwi Husniyati; Ridho Abdillah; Ahsin Shidqi; Husnaini Amiroh; Rendi Rendi; Luthfan Tri Mukti (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study discusses the Islamic legal perspective on the role of wives as breadwinners, based on the fact that the obligation to provide for the family, which should be the responsibility of the husband, often falls to the wife. To date, many wives play a role in helping their husbands to meet the family's economic needs, and some wives even become the main breadwinners. This study uses a normative juridical approach with a descriptive qualitative research design. Data collection techniques were carried out by examining various relevant literature such as the Qur'an, Hadith, fiqh books, Islamic law books, and scientific journals discussing the Islamic legal perspective on the role of wives as breadwinners. Data analysis was conducted using content analysis, which involved systematically interpreting the content of the source material through a process of categorization and meaning extraction. In Islamic law, providing for the family is the primary obligation of the husband, but economic, social, and cultural conditions often require wives to work to help support the family. This dual role of wives can strengthen household finances, but it can also cause tension and role conflicts. Therefore, balance and mutual understanding are important to maintain harmony.